The transformative role of women leaders in the fight against corruption in Uganda - Norman Sempijja; Emilija Žebrauskaitė (Revista CIDOB d'Afers Internacionals, 2021)
Ugandan women have managed to emancipate themselves and reach key positions of power in the public sector. However, they still struggle to exert decisive influence in the fight against corruption. This mixed methodology research analyses the root causes of the corruption and their effect on the role of women in fighting this scourge. It concludes that despite achieving greater transparency, the women in power in Uganda have been overwhelmed by the collective perception that the country’s elites are engaged in corrupt practices and by the need for political survival in a patrimonial political system. Nevertheless, when given space and agency, they have been transformative. Such was the case with the fight against HIV and the changes Allen Kagina inspired in the Revenue Authority and the National Roads Authority.